Toward cycle time reduction in manufacturing SMEs: Proposal and evaluation. Issue Volume 30:Issues 3(2018) (3rd July 2018) - Prashar, Anupama
ABSTRACT: This article presented an exploratory study to conceptualize and validate a Lean Six Sigma (LSS) deployment roadmap for manufacturing small and medium-sized enterprises (SMEs). The existing LSS theories were developed for large businesses and ignore the restrictive resource capabilities of SMEs. The LSS framework developed based on the conceptual insights consisted of three parts: constructs, methodology, and tools. The application of proposed framework was illustrated through the case study of a small-scale engineering enterprise facing chronic delays in the delivery of one of the engineering assemblies leading to client dissatisfaction. The case findings showed an annual cost saving of USD 54, 600 in form of eliminated liquidated damages.